A muse of the modernity: Laura Mendez de Cuenca (1853-1928) - Bazant, Milada (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper discusses the biographical, literary and educational career of one of the first feminist in México, Laura Méndez de Cuenca. A liberal and modern woman, single mother, she dared to transgress the social catholic rules of her time and she lived a free life but paying a high price for that freedom. Her legacy is a 2000 pages treatise on education and literary compendium of all genres.